Model Pelayanan Administrasi Kependudukan Loket Desa Bebas Calo di Kabupaten Wonogiri - Ardita Dinda Isnaeni (Universitas Sebelas Maret, 2021)
This study describes and examines several problems, first, in the implementation of population administration services at the Loket Desa in Wonogiri Regency are touts-free. Second, the model of population administration service at the Loket Desa that is free of touts that can be applied by the Population and Civil Registration Office of Wonogiri Regency. This research is a descriptive empirical research using an inductive approach. The types of data used in this study are primary and secondary data. Data collection techniques used through documentation studies, interviews and observations. The data analysis of this research is data reduction, data presentation, conclusion drawing and verificationThe widespread use of touts' services are still found in population administration services. This happened because people feels that services in population administration must go through complicated and long bureaucratic procedures. In fact, as bureaucratic reforms and government policies progressed, population administration services became easy, simple and free. On the other hand, using the services of touts makes management costs expensive and becomes an illustration of the low quality of service. Based on these problems, we need a new innovation that is